The promise of neo-functionalism beyond Europe: the case of Japan–South Korea relations - Batko, Agnieszka (Asia in World Politics: Past, Present, and Future, 2021)
Northeast Asia accounts for one of the most well-developed regions with the world’s three largest economic powers. However, as former South Korean President Park Geun-hye described, it also constitutes a “paradox.” On one hand, states are able to successfully cooperate on the economic basis. On the other hand, there are a number of obstacles, involving primarily unresolved historical issues and security concerns, that impede further regional collaboration. The aim of the article is to analyse the process of regional integration in Northeast Asia, with particular focus on Japan – Republic of Korea relations, through the lenses of neo-functionalism. The essay seeks to determine whether this approach could lead to increasing transnational ties in the region and ultimately improve international relations on bilateral and multilateral basis. Neo-functional theory of regional integration has been mostly applied to research on the European integration process. Consequently, there have been few attempts of testing its assumptions in other regions. Nevertheless, there seems to be substantial evidence to perceive neo-functionalism as a promising theoretical approach beyond Europe. Since neo-functionalists place supranational, transnational and sub-national actors at the centre of the analysis, the article, apart from the economic dimension, will elaborate on the potential of existing international structure, namely the Trilateral Cooperation Secretariat.